2017
DOI: 10.4103/0970-1591.195724
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary sarcoidosis: An essential review for the practicing clinician

Abstract: Introduction:Sarcoidosis is a multisystem disease that commonly involves the lungs, but may also present with extrapulmonary manifestations. Genitourinary (GU) tract involvement has been traditionally thought to be rare, but that view may underestimate the true prevalence of the disease due to the often, silent presentation thereof.Methods:The literature pertaining to sarcoidosis from the general systemic point of view, etiology and therapy and with regard to specific organs was reviewed by identifying key wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 67 publications
1
14
2
1
Order By: Relevance
“…Sarcoidosis manifestation in the genitourinary system is extremely rare and is estimated to affect less than 0.2% of patients [ 1 ]. In the largest review of 60 cases of sarcoidosis involving the male reproductive system, it was shown that epididymal lesions were found in 73% of patients, in testicles in 47%, in the spermatic cord in 8%, and the prostate in 3% [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcoidosis manifestation in the genitourinary system is extremely rare and is estimated to affect less than 0.2% of patients [ 1 ]. In the largest review of 60 cases of sarcoidosis involving the male reproductive system, it was shown that epididymal lesions were found in 73% of patients, in testicles in 47%, in the spermatic cord in 8%, and the prostate in 3% [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis is a multi-system disease characterized by the formation of non-caseating granulomas in various organs. The lungs remain the most frequently affected organ, whereas lesions in the genitourinary system are found in less than 0.2% of patients [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Block et al . and Kava[1] review the urological manifestations of sarcoidosis and show that the disease may involve multiple organs including the adrenal, kidneys, ureter, bladder, prostate, urethra, penis, and the scrotal structures. It often mimics malignancy in the form a mass lesion.…”
Section: Genitourinary Sarcoidosismentioning
confidence: 99%
“…The most commonly involved extrathoracic organ is the skin [ 1 ]. On the other hand, the involvement of the genitourinary tract is considered rare [ 4 ]. It occurs in less than 0.2% of all clinically diagnosed cases of sarcoidosis, with the epididymis, followed by testicles, being the most frequently involved sites [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with testicular involvement usually present with a non-painful, diffuse nodular mass [ 2 ]. Testicular cancer and sarcoidosis have their peak incidence in the same age group and a similar presentation, so they can be very difficult to distinguish [ 4 , 5 ]. Therefore, although rare, genitourinary sarcoidosis should be part of the differential diagnosis of urological conditions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%